The Effect of Capital Structure on Company's Performance - Hendra Gunawan; Septi Riska Daulay (Journal of Applied Accounting and Taxation, 2016)
The research determine the effect of capital structure on company performance. The population in this study is the Indonesian Stock Exchange listed company. The final sample was obtained 756 companies over three years. The sample was selected using purposive sampling technique with some criteria. The independent variable measured of capital structure with long term debt and short term debt and dependent variable measured of company performance with ROA and ROE. Research hypotheses were tested by multiple linear regression analysis. Based on test results, it was found that the long term debt and short term debt has a significant to company performance. The limitations of this research was only three years the company's data, does not include other variables that have a significant effect the dependent variable.